A fuzzy analytic hierarchy process for assessing biodiversity conservation - Mendoza, G.A.; Prabhu, Ravi (Kluwer Academic Publishers, 2001)
Biodiversity conservation, as one criterion for evaluating forest sustainability, is assessed using a fuzzy analytic hierarchical framework organised around three concepts; criteria, indicators, and verifiers. Following this hierarchical framework, a biodiversity conservation index model was developed as a two step process. First, analysis is done at the indicator level to estimate the cumulative impacts of the verifiers, which are modelled as fuzzy variables. At the second level, the cumulative impacts of the indicators are measured. In both levels, the analytic hierarchy process is used to estimate the relative importance of each element in the hierarchy. Biodiversity experts then provided opinions, through pairwise comparisons, for elements at each level in the hierarchy, producing estimates of their relative importance. Based on these importance values, a composite biodiversity conservation index is calculated by combining index values from both levels of the hierarchy. To demonstrate this approach, a case study involving a forest located in Kalimantan, Indonesia was used.